(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Access control is very important in cloud data sharing. Especially in the domains like healthcare, it is essential to have access control mechanisms in place for confidentiality and secure data access. Attribute based encryption has been around for many years to secure data and provide controlled access. In this paper, we proposed a framework that supports circuit and attributes based encryption mechanism that involves multiple parties. They are data owner, data user, cloud server and attribute authority. An important feature of the proposed system is the verifiable delegation of the decryption process to cloud server. Data owner encrypts data and delegates decryption process to cloud. Cloud server performs partial decryption and then the final decrypted data are shared for users as per the privileges. Data owner thus reduces computational complexity by delegating decryption process cloud server. We built a prototype application using the Microsoft.NET platform for proof of the concept. The empirical results revealed that there is controlled access with multiple user roles and access control rights for secure and confidential data access in cloud computing.